1999
DOI: 10.1152/jappl.1999.86.2.687
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of femoral blood gases and muscle near-infrared spectroscopy at exercise onset in humans

Abstract: We hypothesized that near-infrared spectroscopy (NIRS) measures of hemoglobin and/or myoglobin O2 saturation (IR-SO2) in the vascular bed of exercising muscle would parallel changes in femoral venous O2 saturation (SfvO2) at the onset of leg-kicking exercise in humans. Six healthy subjects performed transitions from rest to 48 +/- 3 (SE)-W two-legged kicking exercise while breathing 14, 21, or 70% inspired O2. IR-SO2 was measured over the vastus lateralis muscle continuously during all tests, and femoral venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 14 publications
(39 reference statements)
6
73
0
Order By: Relevance
“…Surprisingly, the Mb contributes nearly 50% to the NIRS deoxy signal (Table 1). Researchers usually ignore the Mb contribution in human muscle experiments [14,18]. Previous rat hindlimb experiments that applied chemical infusion to modify the muscle O 2 uptake have suggested that 90% of the NIRS signal comes from Hb [9].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the Mb contributes nearly 50% to the NIRS deoxy signal (Table 1). Researchers usually ignore the Mb contribution in human muscle experiments [14,18]. Previous rat hindlimb experiments that applied chemical infusion to modify the muscle O 2 uptake have suggested that 90% of the NIRS signal comes from Hb [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that muscle NIRS measures manifest significant special heterogeneities across the contracting quadriceps (29), so it is unclear whether a lower [HHb] amplitude during moderate-intensity exercise and the increased TOI during severe-intensity exercise at a discrete site of the vastus lateralis is reflective of an improved matching between muscle O 2 delivery and muscle V O 2 across the contracting quadriceps. Indeed, some studies report good agreement between NIRS markers of muscle oxygenation and mixed venous PO 2 or oxygenation (39), while other studies do not (38). It has also been suggested that the interpretation of NIRS data may be complicated by increased skin blood flow (30,40), as develops during exercise.…”
Section: Severe-intensity Exercisementioning
confidence: 99%
“…The only condition that showed a significant correlation was during the hypoxic breathing condition; normoxic and hyperoxic conditions showed NIRS oxygenation levels increasing while femoral venous oxygen saturation decreased. Due to the marked differences in NIRS oxygenation and femoral venous oxygenation, McDonald et al (1999) concluded that NIRS was not an accurate assessment of venous blood oxygenation during exercise. It should be noted, however, that there are several limitations to this study.…”
Section: Validationmentioning
confidence: 99%